The quality of Australia's higher education system : how it might be defined, improved and assured. - Probert, Belinda (Office for Learning and Teaching, 2015)
This discussion paper sets out to engage the widest possible audience in an informed and critical debate about why higher educational quality in Australia needs to be demonstrated, and what we have learned from the past two decades of policy and practice. It begins by noting (in Part 2) how the purposes of higher education have inevitably changed as we have moved from an elite system towards universal participation, requiring us to redefine our definitions of quality. In Part 3 the key ideas about quality in higher education that have shaped both government policy and institutional practice are reviewed The paper moves in Part 4 to an historical analysis of the different approaches to quality assurance that have been adopted since the early 1990s. In the final part of the discussion paper the possible elements of a quality regime for the future of Australian higher education are outlined and critically evaluated, building on what we can learn from our own experience and the higher education systems of the US and the UK.[Executive summary, ed].